Control allocation for electric vehicles with Brake-by-Wire to optimise safety and energy efficiency across full envelope of operation - Li, Yiyuan; Siampis, Efstathios (Institute of Electrical and Electronics Engineers (IEEE), 2025)
To enhance vehicle stability and maximise energy efficiency, this paper presents a novel control allocation strategy for electric vehicles (EVs) equipped with a brake-by-wire system, which can independently allocate tractive and brake torques on 4 in-wheel motors and friction brakes. The proposed approach integrates a real-time optimisation algorithm that dynamically allocates torques to individual motors/brakes by considering the tyre, motor and friction brake dynamic limits. It also employs an asymmetrical cost function, penalising positive and negative motor torques differently to maximise regenerative braking energy recovery. Simulation results using a high-fidelity vehicle model demonstrate significant improvements in vehicle handling and energy efficiency performances compared to the traditional control allocation method. This paper therefore showcases how to construct a global optimal wheel torque strategy considering both performance-oriented and energy-efficient EV applications.
Keywords: 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; 4010 Engineering Practice and Education; 7 Affordable and Clean Energy; optimal control allocation; safety and energy efficiency; tyre and actuator dynamic limits; asymmetrical cost function